Pengaruh Budaya Organisasi Dan Kompetensi Pedagogik Terhadap Kinerja Guru SMPN Sekecamatan Muara Beliti - Maryoto; Danim, Sudarwan; Connie (Manajer Pendididikan, 2024)
The purpose of the study was to analyze the effect of organizational culture and pedagogical competence on the performance of SMPN teachers in Muara Beliti sub-district. Associative quantitative research type. The study population was 80 people. The sampling technique was carried out with saturated sampling technique, where the number of samples used in this study was 80 people. Data analysis techniques are simple regression analysis, multiple regression analysis, Determination Test (R2) and F Test. The conclusion of this study 1) There is an influence of organizational culture on performance of 12.8 or 12.8%. In other words, Organizational Culture has a contribution of 12.8% in shaping the level of Teacher Performance. 2) There is an effect of Pedagogic competence on teacher performance of 26.8 or 26.8% Pedagogic competence has a contribution of 26.8% in shaping the level of Teacher Performance. 3) There is an influence of organizational culture and pedagogical competence on the performance of SMPN teachers in Muara Beliti sub-district by 32.2 or equal to 32.2%. This figure means that the Organizational Culture variable (X1) and the availability of Pedagogical Competence (X2) simultaneously (together) affect the Teacher Performance variable (Y) by 32.2% While the rest (100% - 32.2% = 67.8%) is influenced by other variables outside of this regression equation or variables not examined.